Demonstration of ghost communication with an encrypted speckle. (May 2022) - Luo, Chunling; Guo, Fumin; Wan, Wenxiu; Fang, Yuqian; Wang, Peilin; Huang, Xiaoyan
Highlights: A novel kind of ghost communication (GC) scheme has been developed to improve the security of the optical encryption based on CGI by utilizing an encrypted speckle. In this paper, the image segmentation method is introduced for the first time in the CGI scheme to effectively realize the high security level of the optical encryption. Due to well random and diversified features of the speckle patterns, the security of the GC system can be significantly improved. We have experimentally demonstrated the resisting capability of our GC system and found that it possesses well robustness against the strong scattering medium, which will be very helpful for the real application of the optical secure communication in the hostile environment. Our proposed GC scheme is capable of increasing security of the optical encryption without adding any complex algorithm or device in the CGI system, thus this approach possesses good compatibility. Abstract: Ghost imaging (GI) is an indirectly optical imaging technique in which a sharp image of an unknown object hidden in harsh environments can be acquired only using a bucket detector, which offers great potential applications in the fields of computational imaging and optical secure communication. Based on the computational ghost imaging (CGI) scheme and the image segmentation method, here we propose a novel kind of ghost communication (GC) approach, where a part of image information to be encrypted is non-conspicuously concealed into an illuminating speckle pattern based on the image hiding method, the other part is encoded into an intensity vector with the bucket detector. Important features, such as the feasibility of our proposal, vulnerability to eavesdropping, and ability to resist noise attack, are experimentally verified and discussed in detail. In contrast to the previously optical encryption based on CGI, the experimental results reveal that the security can be largely enhanced by introducing the encrypted speckle into our GC approach. Our work thus offers a concise way to improve the security and enriches the knowledge of the optical secure communication based on CGI.